EKSPLORASI KARAKTERISTIK TENUN CUAL SEBAGAI IDENTITAS MASYARAKAT MELAYU SAMBAS DAN TANTANGAN DALAM UPAYA PELESTARIANNYA - Fatihah, Nur Astri; Trisnawati, Hikmah; Hidayat, Andri; Jagat, Lang; Elviana, Vivin (Borneo : Journal of Islamic Studies, 2024)
Sambas Traditional Weaving Craft is one of Indonesia's cultural riches and heritages that has high artistic and cultural value. Sambas Traditional Weaving Craft is a source of livelihood for the local community, as well as an important representation of cultural identity and historical heritage for the Sambas Malay community. This study aims to identify the characteristics of Sambas Cual Weaving and identify challenges in its preservation efforts. The approach used is qualitative research with data collection methods through observation, semi-structured in-depth interviews, and secondary data collection (document studies). Informants were selected purposively. The results of the study show the unique characteristics of Sambas Cual Weaving, which include aspects of its distinctiveness and differences, manufacturing techniques, motifs and patterns as well as the texture and color of the fabric. The main challenges faced in efforts to preserve Sambas Cual Weaving include: ageing craftsmen and increasingly rare skills, declining interest from the younger generation, challenges in economic feasibility and sustainability, and previous knowledge and skills that are not perfectly inherited.